Bioactive compounds and DPPH antioxidant activity of underutilized macroalgae (Sargassum spp.) from coastal water of Makassar, Indonesia - SANTIA GARDENIA WIDYASWARI; METUSALACH METUSALACH; KASMIATI KASMIATI; NURSINAH AMIR (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Widyaswari SG, Metusalach, Kasmiati, Amir N. 2024. Bioactive compounds and DPPH antioxidant activity of underutilized macroalgae (Sargassum spp.) from coastal water of Makassar, Indonesia. Biodiversitas 25: 176-182. This study focuses on determining the chemical component and potential of two species of macroalgae (seaweed) Sargassum spp., i.e., Sargassum polycystum and Sargassum ilicifolium from the coastal waters of Makassar City, South Sulawesi, Indonesia. Several macroalgae are highly cultivated and exported; however, these species of Sargassum remain underutilized due to limited studies on their potential. Brown algae (Phaeophyceae), especially Sargassum spp., contain secondary metabolites known for their health-promoting properties, including antioxidant effects, inhibiting oxidative stress, lowering blood pressure, and improving the immune system. The investigation analyzes the nutritional components and bioactive substances in Sargassum spp. harvested from the Makassar City coastal waters, South Sulawesi, Indonesia. Nutritional content was analyzed using proximate analysis. Phytochemical screening was conducted based on the method by Harborne method. Antioxidant activity was performed using the DPPH method. Total phenolic/flavonoid content based on spectrophotometric method. The investigation reveals the primary chemical composition of Sargassum polycystum showing the presence of valuable secondary metabolites such as alkaloids, flavonoids, phenol hydroquinone, and reactive saponins. Sargassum ilicifolium contains flavonoids, phenol hydroquinone, tannins, and steroids. The IC50 values for the antioxidant activity of S. polycystum and S. ilicifolium were 51.34 ppm and 51.25 ppm, respectively. The compounds in these seaweeds might be beneficial in promoting health. These findings suggest the possibility of underutilized seaweeds as a natural source of antioxidants in food and non-food industries.